Save the Children Priorities and Key Learnings from Early Warning & Early Action Practices on Drought Hazard in Pastoralist Communities of Somali Region, Ethiopia - Masresha, Wasihun (Save the Children, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025